The Way Forward in the Energy Transition; Good Practices and Challenges at Wageningen University & Research - Maters, Erna; Vaas, Django Milner; Luttik, Joke; Leeuwen, Wouter van (Universitas Diponegoro, 2024)
Reducing greenhouse gas (GHG) emissions due to changes in energy used in buildings is the most successful part of Wageningen University & Research’s (WUR) climate policy. In this article the authors evaluate sustainable energy measures and identify key success factors, based on internal documents, discussions with stakeholders, and relevant literature. The role of government and stakeholders has been important, as were the technical possibilities to take a major step with constructing the heat and cold storage on campus. Geopolitical factors also played a role, in particular the war in Ukraine, which increased energy prices, acutely reinforcing the need for energy savings. In addition to saving energy, WUR aims to contribute to the energy transition by generating green electricity with wind turbines and solar panels. Furthermore, electricity used from the grid is offset with wind energy through Dutch guarantees of origin (GVOs), allowing us to offset GHG emissions for electricity at zero. Yet, there are other reasons to save as much as possible on electricity use. In addition to environmental considerations, congestion of the electricity grid plays a role, which is largely associated with the energy transition. Looking ahead, we describe further potential energy reduction opportunities and related challenges. As described in the Rough Outline of WUR Energy Transition 2050 [1], WUR provides clear targets and possible sets of measures to achieve these targets. Challenges include the uncertainty surrounding technological solutions and the availability of funding. We recently expanded our carbon footprint to include Scope 3 emissions of purchased goods and services. An additional challenge is the reduction of implicit energy use through the purchasing chain.